Bacterial vaginosis: impact of treatment and associated risk factors: a cross section study - Sharma, Meeta; Metre, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Bacterial vaginosis (BV) is a condition caused by an overgrowth of normal vaginal flora. Many socio-demographic factors are associated with bacterial vaginosis. Antibiotic resistance to some organism is a challenge in treatment of bacterial vaginosis. Methods: This cross-sectional study was conducted including 100 women with reproductive age group presenting with complain of vaginal discharge. After clinical examination, vaginal swab was collected of patients who gave consent for same. Socio-demographic characteristics were recorded and risk factors were assessed. The slide smears were prepared from vaginal swabs, and the slides were heat-fixed, gram-stained and examined under oil immersion objective. Each slide was then graded as per the standardized quantitative morphological classification method developed by Nugent. Identification of bacteria to genus and/or species level was done by employing an array of routine biochemical tests for Gram-positive bacteria for Gram-negative bacteria. In vitro antibacterial susceptibility testing of bacterial isolates was performed by the Kirby-Bauer disc diffusion method. Sensitivity test results were interpreted according to the Clinical and Laboratory Standards Institute. Results: High incidence of bacterial vaginosis was found among 35 to 45 years age group (63.8%), married females (63.9%), illiterate (100%), females with more than 3 sexual partners (66.7%), those with any co-morbidity (80%) and females not using any method of contraception (100%). E coli (28%) was predominant organism causing bacterial vaginosis followed by Gardenella vaginalis (20%) among the gram-negative bacteria. Among gram positive bacterial S. pyogen (2%) and S. agalactiae (2%) were present. Drug resistance to trimethoprim/sulfamethxazole, erythromycin, cefoxitin, ceftriaxone and gentamycin was detected. Conclusions: Higher age, illiteracy, multiple sexual partners and absence of contraception use can increase risk of bacterial vaginosis. Gram negative organisms are common cause of bacterial vaginosis and they are resistant to trimethoprim/sulfamethoxazole and erythromycin.